Вибір номінації адресата мовлення сучасним українським чоловіком (лексико-семантичні особливості) - Гаврилащук, О. (Лексикографічний бюлетень, 2011)
The article deals with the peculiarities of influence of gender factor on the nomination choice of addressee that is reflected in fiction texts. In particular, a gender marked use of lexemes connected with addressee in the interpreted inner indirect speech has been analysed. The lexico-semantic classification presents the nominations of addressee in a man’s speech, with the distinction of the active – addressee’s speech (when the speaker can’t take part directly in the communication, which is recreated in the inner speech). This research has been cjnducted on the materials of the modern Ukrainian fiction.